2010
DOI: 10.1002/jemt.20958
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the physical cluster‐size distribution within materials using atom‐probe

Abstract: A limiting characteristic of the atom-probe technique is the nondetection of ions and this embodies a significant "missing information" problem in investigations of atomic clustering phenomena causing difficulty in the interpretation of any atom-probe experiment. It is shown that the measurable cluster-size distribution can be modeled by a mixed binomial distribution. A deconvolution method based upon expectation-maximization (EM) algorithm is presented to obtain the original physical distribution from an effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Methods for identifying clusters (nanometer-scale concentrations of one or more element) in atom-probe data have been the subject of various approaches (Blavette et al 1988;Vurpillot et al 2004;Miller and Kenik 2004;Miller et al 2007;De Geuser et al 2006;Cerezo and Davin 2007;Marquis and Hyde 2010;Stephenson et al 2011;Serizawa and Miller 2013). The full details of these approaches are beyond the scope of this paper.…”
Section: Constructing the Three-dimensional Imagementioning
confidence: 98%
“…Methods for identifying clusters (nanometer-scale concentrations of one or more element) in atom-probe data have been the subject of various approaches (Blavette et al 1988;Vurpillot et al 2004;Miller and Kenik 2004;Miller et al 2007;De Geuser et al 2006;Cerezo and Davin 2007;Marquis and Hyde 2010;Stephenson et al 2011;Serizawa and Miller 2013). The full details of these approaches are beyond the scope of this paper.…”
Section: Constructing the Three-dimensional Imagementioning
confidence: 98%
“…However, in the case of alloys, accurate restoration of the missing atoms, at least in a broader statistical sense, is an exciting yet now achievable goal. Limited detection efficiency can introduce serious ambiguity into the interpretation of the results (Moody et al, 2008; Stephenson et al, 2010), and the capacity to restore this missing data will enable a far more complete and quantitative characterization of material nanostructure. If the missing data can be replaced with a high degree of confidence, one is now dealing with a complete 3D atomistic rendering of a material, allowing for highly accurate quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…With high enough detection efficiency cluster size distributions can be estimated to real clusters size distributions. [103] Another limitation is the loss of crystallographic information, strongly dependent on the alloy, and À experimental parameters; in some regions of the reconstruction can lattice planes of certain directions be resolved (pole regions À poles). Although, in special cases, APT can be used to clarify occupancy of elements on sublattices [104,105] or it has been shown that crystallographic arrangement of atoms may be regained altogether.…”
Section: Functionalitymentioning
confidence: 99%